Gender Differences in Desistance From Crime: How Do Social Bonds Operate Among Formerly Incarcerated Emerging Adults?. Issue 1 (January 2018) - Abrams, Laura S.; Tam, Christina C.
Life course theory suggests that the social bond of marriage can serve as a pivotal turning point toward the termination of criminal activity, particularly for men. Yet limited research has investigated how young adult men and women utilize social bonds forged outside of marriage to facilitate desistance from crime. This study explored gender differences in how formerly incarcerated emerging adults navigate and utilize their social bonds with peers and romantic partners on the journey toward criminal desistance. Two semi-structured qualitative interviews and a social mapping exercise were conducted with 14 emerging adults (seven men and seven women) with extensive histories of juvenile incarceration. With regard to friends, the young women found peer support often inconsistent, leading to an overarching theme of self-reliance. Some of the young men used peer supports with an overarching theme of reciprocity, while others used peer supports very sparingly in order to avoid contact with criminal associations or potential danger. With regard to romantic partnerships, these relationships proved much more supportive of desistance goals for the young men and the contrary was the case for the young women in heterosexual partnerships. These findings add to a growing literature about the process of desistance for emerging adults.